Unveiling the Issues: Feminist Legal Theory's Critique on Rape Formulation in Indonesia - Al Ma'shumiyyah, Maryamul Chumairo' (Universitas Islam Negeri Walisongo Semarang, 2023)
The crime of rape remains a crucial issue in Indonesia. The formulation of the rape offence regulated in Article 285 of the Criminal Code has several weaknesses. It is considered no longer in line with current legal developments, leading to suboptimal handling of rape cases. This research further analyzes the problematic formulation of the crime of rape in various laws and regulations, especially in the Criminal Code, and the reformulation and redefinition of rape in the new Criminal Code using the Feminist Legal Theory approach. This is a doctrinal study utilizing a literature review. The results indicate that the formulation in Article 285 of the Criminal Code has weaknesses, including issues related to the scope of rape, the conventional interpretation of intercourse, and limitation to a specific gender. Rape is closely linked to gender relations' inequality, placing female rape victims at risk of victimization from various parties. Therefore, it is essential to shape laws with a gender perspective.Tindak pidana perkosaan masih menjadi permasalahan krusial di Indonesia. Formulasi delik perkosaan yang diatur dalam Pasal 285 KUHP memiliki sejumlah kelemahan dan dianggap tidak lagi sesuai dengan perkembangan hukum, sehingga penanganan kasus perkosaan tidak optimal. Penelitian ini mengkaji lebih lanjut mengenai problematika formulasi tindak pidana perkosaan dalam berbagai peraturan perundang-undangan, khususnya dalam KUHP, serta reformulasi dan redefinisi perkosaan dalam pembahasan KUHP baru dengan menggunakan pendekatan Feminist Legal Theory. Penelitian ini bersifat doktrinal dan menggunakan studi pustaka. Hasilnya menunjukkan bahwa formulasi dalam Pasal 285 KUHP memiliki kelemahan, seperti ruang lingkup perkosaan, pemaknaan konvensional tentang persetubuhan, dan keterbatasan pada satu gender tertentu. Perkosaan terkait erat dengan ketidaksetaraan dalam relasi gender, yang membuat perempuan korban perkosaan rentan terhadap viktimisasi dari berbagai pihak. Oleh karena itu, penting untuk membentuk hukum yang berperspektif gender.